An Analysis Of Language Style On Adele's Instagram Account From July 2020 to July 2022: Language Style on Adele’s Instagram Account from July 2020 to July 2022 - Wuri, Sintia; Muntuuntu, Meity; Maru, Mister Gidion (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2025)
This research’s purposes is to analyze the language style that is used by Adele in her Instagram’s captions that is based on Joos’ theory of language style. The data was taken by the researcher from Adele’s Instagram’s captions that she had posted from July 2020-2022. This research was done qualitatively using Miles & Huberman’s data analysis technique. The result of this research shows that Adele’s most dominant language style is casual language style. As the researcher found that, from 50 captions that she posted along the 2 year, she was mostly using casual language style with 29 captions, followed by 12 formal language style, 8 intimate language style and 1 consultative language style, while she never used frozen language style in her captions. From those data then the researcher pulled out a conclusion that Adele’s most dominant language style in her Instagram’s captions is casual language style.